Dynamic and sound radiation characteristics of a non-uniformly heated isotropic plate. (April 2022) - Vaiduriyam, Arul Raj; Chinnapandi, Lenin Babu Mailan; Pichaimani, Jeyaraj
The influence of non-uniform heating on the anisotropic plate's dynamic and acoustic response characteristics is investigated numerically. The effect of non-uniform heating on the plate is accounted in the form of pre-stress developed on the plate due to non-uniform heating of the plate. The influence of structural boundary conditions, nature of temperature variation, and level of temperature on vibration and acoustic response characteristics are investigated in detail. Thermal buckling strength and fundamental buckling mode are highly sensitive to the nature of temperature variation across the plate. Free vibration mode shapes of the plates with high aspect ratio and free edges are changing their pattern with an increase in temperature. The resonant amplitude of sound power radiated associated with a particular mode is dominated by vibration nodes and anti-nodes shifting relative to the excitation location. Further, an increase in sound power level with an increase in temperature is observed clearly in the lower octave frequency bands.